Organelle genomes reveal adaptive evolution and phylogenetic position of the endangered Primula mallophylla - Li, Wenqiao; Wang, Le; Zuo, Youwei; Zhang, Huan; Zhang, Xiao; Yang, Lingxiang; Zhang, Jiabin; Zheng, Fengyuan; Deng, Hongping (Frontiers in Plant Science, 2025)
IntroductionSpecies of Primula section Proliferae are predominantly distributed in alpine environments above 2,000 meters and represent an important group for studying environmental adaptation and phylogenetic evolution. Primula mallophylla, holds important ecological, ornamental, and conservation value. However, genomic resources for this species remain unavailable, hindering further research on its genetic evolution and conservation strategies.MethodsIn this study, we sequenced and assembled the complete mitochondrial and chloroplast genomes of P. mallophylla for the first time. Comprehensive analyses were conducted on their structural characteristics, repetitive sequences, RNA editing site prediction, codon usage bias, intracellular gene transfer, phylogenetic inference, and selective pressure.ResultsThe results show that both the mitochondrial and chloroplast genomes exhibit typical master circular structures, with sizes of 340,219 bp and 150,733 bp, respectively. The mitochondrial genome has more abundant repetitive sequences and has undergone genomic rearrangements. There are only 9 MTPTs between mitochondria and chloroplasts, totaling 2,028 bp. In the regulation of mitochondrial genome expression, we predicted 475 RNA editing sites, with ccmB and mttB showing the highest potential editing frequencies. We found that P. mallophylla exhibits similar codon usage bias to most plants, and based on ENC-GC3s analysis, some genes appear to be under natural selection. Chloroplast genes rpl2, rpl22, rbcL, and ndhB exhibit branch-specific positive selection in Primula, reflecting adaptive evolution of photosynthesis and protein synthesis functions in high-altitude environments. Based on phylogenetic trees constructed from PCGs, Primulaceae are most closely related to Ebenaceae. Furthermore, phylogenetic analysis based on chloroplast genomes and PCGs of Primula species showed that sect. Proliferae is not monophyletic, with P. stenodonta being a sister species to P. mallophylla.DiscussionThese findings provide crucial genomic resources and insights into the adaptive evolution of P. mallophylla, while also clarifying phylogenetic relationships within sect. Proliferae and Primulaceae, thereby offering valuable guidance for conservation strategies and further evolutionary studies.